Peran Job Satisfaction Sebagai Mediasi Pengaruh Internal (CSR) Internal Terhadap Happiness Management Karyawan - Hidayat, Muhammad Fikri; Kristanto, Rudi Suryo (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The research on employees belonging to the millennial age group is an intriguing subject to delve into, as these individuals possess distinct attributes and traits. Employee satisfaction is of utmost importance to companies, and one way to ensure employee happiness is by providing internal Corporate Social Responsibility (CSR). In this regard, a study has been conducted to analyze the mediating role of job satisfaction on the relationship between internal CSR and happiness management, with respondents belonging to the millennial age group (17 to 40 years). The test results have revealed that internal CSR has a positive impact on happiness management, and job satisfaction also has a positive influence on the same. However, an interesting finding is that job satisfaction has a mediating role in the relationship between internal CSR and happiness management